Production of π0 and [eta] mesons up to high transverse momentum in pp collisions at 2.76 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2017)
The invariant differential cross sections for inclusive π0π0π ^{0} and ηηη mesons at midrapidity were measured in pp collisions at s√=2.76s=2.76\sqrt{s}=2.76 TeV for transverse momenta 0.4<pT<400.4<pT<400.4<p_{T}<40 GeV/c and 0.6<pT<200.6<pT<200.6<p_{T}<20 GeV/c, respectively, using the ALICE detector. This large range in pTpTp_{T} was achieved by combining various analysis techniques and different triggers involving the electromagnetic calorimeter (EMCal). In particular, a new single-cluster, shower-shape based method was developed for the identification of high-pTpTp_{T} neutral pions, which exploits that the showers originating from their decay photons overlap in the EMCal. Above 4 GeV/ccc, the measured cross sections are found to exhibit a similar power-law behavior with an exponent of about 6.3. Next-to-leading-order perturbative QCD calculations differ from the measured cross sections by about 30% for the π0π0π ^{0}, and between 30-50% for the ηηη meson, while generator-level simulations with PYTHIA 8.2 describe the data to better than 10-30%, except at pT<1pT<1p_{T}<1 GeV/ccc. The new data can therefore be used to further improve the theoretical description of π0π0π ^{0} and ηηη meson production.
Im Titel wird das Zeichen "0" hochgestellt
Im Titel werden "pi" und "eta" als griechische Buchstaben dargestellt
The ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, S. Schuchmann, J. Stachel, D.F. Weiser, J. Wilkinson, B. Windelband, A. Zimmermann [und weitere]
Gesehen am 02.10.2018